Childhood trauma and violent behavior in adolescents are differentially related to cognitive-emotional deficits - Katembu, Stephen; Zahedi, Anoushiravan; Sommer, Werner (Frontiers in Public Health, 2023)
Converging neurobiological and epidemiological evidence indicates that exposure to traumatic events in the early stages of development, that is, adverse childhood experiences (ACEs), negatively affects the likelihood to be involved in violent behavior later in life. These problems seem to be mediated to some extent by the disruption of executive functions, in particular the ability to inhibit inappropriate actions. Here we aimed to distinguish the contribution of inhibition in non-emotional and emotional situations (i.e. emotion regulation) and assessed the modulating influence of stress, testing Nairobi county high school students. In Experiment 1, neutral and emotional inhibition, working memory, and fluid intelligence were measured alongside questionnaires about ACE and violent behavior. ACE was positively related to both non-emotional and emotional inhibition; in contrast, violent behavior was only related to deficient emotional inhibition. Experiment 2 replicated these relations in an independent sample and assessed whether they would be aggravated after acute experimentally induced stress. Stress did not significantly affect the relation of ACE to non-emotional inhibition and emotion regulation; however, it increased deficits of violent participants in their ability to down-regulate emotions. Together, results suggest that more important than impairments in non-emotional inhibition in driving violent behavior in victims of childhood trauma may be their deficits in emotion regulation, especially under stressful conditions. These novel findings open perspectives towards more targeted research and interventions.